Noble-metal nanoparticle labelling multiplex miRNAs by ICP-MS readout with internal standard isotopes of 115In and 209Bi. Issue 6 (10th February 2021) - Zhang, Fei; Yong, Li; Hua, Xia; You, Fan; Wang, Bin; Feng, Yu-Liang; Mao, Li
Abstract : A small sized (less than 20 nm) noble-metal nanoparticle labelled ICP-MS (NP-ICP-MS) is proposed for high-throughput microRNA (miRNA) determination. Abstract : Inductively coupled plasma-mass spectrometry (ICP-MS) is one of the most powerful techniques for multiplex nucleotide assay owing to the virtue of the high resolution of multiple-elements' mass to charge ratio, in a mass spectrum. Here, a small sized (less than 20 nm) noble-metal nanoparticle labelled ICP-MS (NP-ICP-MS) is proposed for high-throughput microRNA (miRNA) determination. Three miRNA targets – miR-486-5p, miR-221, and miR-21 – in serum, were distinguished by single-stranded DNA (ssDNA) probes labelled with a small sized noble-metal nanoparticle – silver nanoparticles (AgNPs), platinum nanoparticles (PtNPs), and gold nanoparticles (AuNPs). The counting isotopes ion intensity per second (CPS) of the noble-metal label versus internal standard isotope intensity of 115 In and 209 Bi, exhibited good linearity in the range 0.25 pM to 100 pM with correlation coefficients ( R 2 ) of 0.9680, 0.9305, and 0.9418. The specific sandwich-type miRNA assay using the sensitive NP-ICP-MS readout pushed the detection limits down to 0.18 pM for miR-221, 0.23 pM for miR-486-5p, and 0.22 pM for miR-21. And the relative standard deviations (RSDs) for 10 pM target miRNA were less than 3.7%. This work promises a potential ultrasensitive ICP-MS bioassay of multiplex miRNA biomarkers for clinical serum diagnosis.